KAJIAN KEBUTUHAN CHECK-IN COUNTER DOMESTIK PADA JAM SIBUK (PEAK HOUR) DENGAN MENGGUNAKAN SERVICE TIME DI BANDAR UDARA INTERNATIONAL MINANGKABAU PADANG - Akhbar Kurniawan; Indria Sari Purwaningrum; Toni (Politeknik Penerbangan Indonesia Curug, 2019)
Along with the increasing the number of airport service users, service providers are required to be able to maintain the quality of flight service, one of them is service during check-in. The service quality of check-in counter is very influenced by two things, namely the service of check-in process facilities and systems used, therefore it greatly affect service to service users. The desired check-in service is the creation of fast and maximum service, which according to regulations. The check-in process time is 2 minutes 30 seconds, if the operator's check-in counter can meet under the given time, it can overcome the buildup passenger queue. Therefore, it is necessary to analyze the number of check-in counter requirements based on direct survey and calculate the passenger check-in process time during peak hours with the Service Time method, the average processing time to meet the check-in counter needs